2016
DOI: 10.1016/j.biortech.2016.04.099
|View full text |Cite
|
Sign up to set email alerts
|

A methanotroph-based biorefinery: Potential scenarios for generating multiple products from a single fermentation

Abstract: Methane, a carbon source for methanotrophic bacteria, is the principal component of natural gas and is produced during anaerobic digestion of organic matter (biogas). Methanotrophs are a viable source of single cell protein (feed supplement) and can produce various products, since they accumulate osmolytes (e.g. ectoine, sucrose), phospholipids (potential biofuels) and biopolymers (polyhydroxybutyrate, glycogen), among others. Other cell components, such as surface layers, metal chelating proteins (methanobact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
125
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(126 citation statements)
references
References 58 publications
1
125
0
Order By: Relevance
“…In addition, the methanotroph community is rather interesting from the commercial point of view since recent studies have suggested the new methanotroph-based biorefinery concept [186]. Methanotrophs are able to generate multiple products from methane fermentation such as feed supplement, ectoine, sucrose, biofuels, biopolymers, surface layers, metal chelating protein, enzymes and/or heterologous proteins [187]. Nowadays, companies such as Mango Materials are commercializing biomethane to bioplastics [128] since a life cycle analysis has recently shown that biomethane conversion to bioplastics is carbon neutral and energetically and economically feasible [188].…”
Section: Current Limitations In Electromethanogenesis and Proposedmentioning
confidence: 99%
“…In addition, the methanotroph community is rather interesting from the commercial point of view since recent studies have suggested the new methanotroph-based biorefinery concept [186]. Methanotrophs are able to generate multiple products from methane fermentation such as feed supplement, ectoine, sucrose, biofuels, biopolymers, surface layers, metal chelating protein, enzymes and/or heterologous proteins [187]. Nowadays, companies such as Mango Materials are commercializing biomethane to bioplastics [128] since a life cycle analysis has recently shown that biomethane conversion to bioplastics is carbon neutral and energetically and economically feasible [188].…”
Section: Current Limitations In Electromethanogenesis and Proposedmentioning
confidence: 99%
“…Some methanotrophs, including Methylosinus trichosporium OB3b, can use a soluble iron sMMO when copper levels are low, with switchover regulated by copper18. MMOs and methanotrophs have great potential for biotransformations giving a range of products, in bioremediation and for mitigating the release of methane, a potent greenhouse gas, to the atmosphere192021. Understanding copper handling and the expression of either pMMO or sMMO is essential for all these biotechnological applications.…”
mentioning
confidence: 99%
“…It retails in the pharmaceutical industry at approximately US$1000 kg -1 and its production at a global scale accounts for approx. 15000 tones year -1 [9]. In this regard, biotechnologies for the production of ectoine have received increasing attention in the last two decades due to their simpler and highly specific product synthesis in comparison with chemical processes [8].…”
Section: Introductionmentioning
confidence: 99%